2022
DOI: 10.1101/2022.02.05.479245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Annelid functional genomics reveal the origins of bilaterian life cycles

Abstract: Indirect development with an intermediate larva exists in all major animal lineages, and thus larvae are central to most scenarios for animal evolution. Yet how larvae evolved remains disputed. Here we show that changes in the timing of trunk formation underpin the diversification of larvae and bilaterian life cycles. Combining chromosome-scale genome sequencing with transcriptomic and epigenomic profiling in the slow-evolving oweniid Owenia fusiformis, we found that different genes and genomic regulatory elem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 165 publications
(327 reference statements)
0
26
1
Order By: Relevance
“…4d; Supplementary Table 6), including a variety of transcription factors that are markers of particular cells and tissue types (e.g., six3/6, gsc, cdx, AP2, foxQ2 ), required for mesoderm development (e.g., twist, hand2, foxH ) and neurogenesis (e.g., POU4, irxA ), Wnt ligands ( wnt1, wntA and wnt4) , TGF-β modulators ( noggin and BAMBI ), and Notch signalling components ( delta and notch-like ). Stage-specific RNA-seq data covering twelve developmental time-points 33 , from the unfertilized oocyte to the mature larva, confirmed that the expression of all candidate genes upregulates at the time of or just after 4d specification and di-P-ERK1/2 enrichment in this cell (Fig. 4d).…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…4d; Supplementary Table 6), including a variety of transcription factors that are markers of particular cells and tissue types (e.g., six3/6, gsc, cdx, AP2, foxQ2 ), required for mesoderm development (e.g., twist, hand2, foxH ) and neurogenesis (e.g., POU4, irxA ), Wnt ligands ( wnt1, wntA and wnt4) , TGF-β modulators ( noggin and BAMBI ), and Notch signalling components ( delta and notch-like ). Stage-specific RNA-seq data covering twelve developmental time-points 33 , from the unfertilized oocyte to the mature larva, confirmed that the expression of all candidate genes upregulates at the time of or just after 4d specification and di-P-ERK1/2 enrichment in this cell (Fig. 4d).…”
Section: Resultsmentioning
confidence: 53%
“…For GO mapping, the GO terms of differentially expressed genes associated with each comparison were extracted from O. fusiformis reference genome annotation 33 (available at the repository https://github.com/ChemaMD/OweniaGenome). GO enrichment analyses were implemented using the GOseq R package, correcting for gene length bias 62 , and analysing up-regulated and down-regulated genes independently.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the expression dynamics of the Fox genes in O. fusiformis and relate each of these genes to major morphogenetic events during the life cycle of this annelid, we used available stage-specific RNA-seq data covering 14 developmental time points, from the unfertilized oocyte to the juvenile stage (Liang et al 2022). In O. fusiformis , the temporal expression dynamics of the Fox genes seem to correlate with their assignment to clade I and clade II, because most clade II Fox genes are expressed maternally and during the early cleavage stages (i.e., up to the 8-cell stage), while clade I Fox genes tend to show short peaks of expression at single developmental stages, from the 32-cell stage onwards (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%